PELATIHAN PERAKITAN KOMPUTER, INSTALL SISTEM OPERASI DAN PEMASANGAN JARINGAN LOKAL DAN INTERNET UNTUK MEMBANGUN JARINGAN WARNET, PERKANTORAN DAN INTERNET DESA DALAM MENINGKATKAN KEMANDIRIAN SISWA SMK TUNAS PELITA DAN SMK ABDI NEGARA KOTA BINJAI - Akim Manaor Hara Pardede; Novriyenni Novriyenni (Teknik Informatika Universitas Malikussaleh, 2019)
The development of information and communication technology is increasing in accordance with the changing times and needs of today's society, so that almost any activity or work is already subject and applying information technology and communication. The development of information technology and impact to the world of education, so that the public interest to major in computer informatics include Computer Network, Audio Visual, Graphic Design, Information Technology, etc. continue to increase both the level of high school or college level. Many enthusiasts of computer majors resulted in strong competition for the graduates to get jobs, so it needs no efforts to improve the skills and graduate students majoring in computer that does not merely want to find a job but was able to create job. STMIK Kaputama continue to perform activities of teaching, research and community service, see the strong competition of graduates and the needs of society Binjai and surrounding areas, lecturer STMIK Kaputama feel compelled to carry out community service to improve the skills of students SMKTunasPelita and AbdiNegara in the form of training computer assembly, installation of operating systems and installation of local networks and the internet to build a network of internet cafes, offices and internet village in increasing independence. With their training computer assembly, installation of operating systems and the installation of local networks and the Internet, it is expected students SMKTunasPelita and SMKAbdiNegara can further enhance the skills and entrepreneurial spirit so that they are capable of self-employed at the same time create jobs specifically to be able to receive computer repair and network cafe, internet network of offices and internet networks into the village. In addition to their entrepreneurial spirit, especially rural society also helped that the acceleration of information and communication can be further increased.